2018
DOI: 10.1021/acs.est.7b06382
|View full text |Cite
|
Sign up to set email alerts
|

Improved Anti-Biofouling Performance of Thin -Film Composite Forward-Osmosis Membranes Containing Passive and Active Moieties

Abstract: Forward osmosis (FO) has gained increasing attention in desalination, wastewater treatment, and power generation. However, biofouling remains a major obstacle for the sustainable development of the FO process. Both passive and active strategies have been developed to mitigate membrane biofouling. A comprehensive understanding of different strategies and mechanisms has fundamental significance for the antifouling membrane development. In this study, thin-film composite (TFC) FO membranes were modified with poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…The antibacterial property of AgNPs was further investigated by combining pDA and AgNPs to simultaneously achieve both passive and active antibacterial properties [164].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…The antibacterial property of AgNPs was further investigated by combining pDA and AgNPs to simultaneously achieve both passive and active antibacterial properties [164].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…It established a practically valid characterization method, which quantifies the vulnerability of the FO membranes to hydraulic pressure. Qi, Hu, Liu, An, and Bar-Zeev (2018) performed an investigation of the anti-biofouling performance both in static and dynamic conditions, of TFC FO membranes modified with polydopamine (PDA) coating as passive antibacterial moiety and silver (Ag) NP as active antibacterial moiety. It was reported that in static exposure, the PDA-coated membranes exhibited great passive anti-adhesive property, and the Ag NP generated membranes presented both of excellent passive and anti-adhesive properties and antibacterial performance.…”
Section: Fomentioning
confidence: 99%
“…Recently, the anti-biofouling of the FO membrane has been investigated and reported. Hu and coworkers mentioned that dopamine-assisted silver nanoparticles(Ag NPs) coating on the membrane surface reveals that biofilm is significantly thinner than the pristine membrane and 97% lower number of Pseudomonas aeruginosa attached in the Ag NPs coated FO membrane [44].…”
Section: Introductionmentioning
confidence: 99%